2017
DOI: 10.1021/acs.molpharmaceut.7b00253
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and Systemic Disposition of Diclofenac under Fasted and Fed State Conditions Supporting the Evaluation of in Vitro Predictive Tools

Abstract: This study aimed to gain further insight into the gastrointestinal disposition of the weakly acidic BCS class II drug diclofenac and the implications for systemic drug exposure in humans under fasted and fed state conditions. For this purpose, gastrointestinal and blood samples were collected from healthy volunteers after oral intake of a commercially available tablet of the potassium salt of diclofenac (i.e., Cataflam) in different prandial states. Subsequently, these in vivo data served as a reference for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
23
1
Order By: Relevance
“…The different gastric acidity in fasted and fed conditions might lead to differences in oral drug dissolution and the speed of precipitation within the gastrointestinal tract. [32] Correspondingly, the peak plasma concentration of diclofenac under fed conditions was reported to be significantly lower and the time to peak plasma concentration was significantly longer compared to fasted conditions. [23] The state of food intake was not standardized in our study, which might have altered absorption and bioavailability rates of diclofenac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different gastric acidity in fasted and fed conditions might lead to differences in oral drug dissolution and the speed of precipitation within the gastrointestinal tract. [32] Correspondingly, the peak plasma concentration of diclofenac under fed conditions was reported to be significantly lower and the time to peak plasma concentration was significantly longer compared to fasted conditions. [23] The state of food intake was not standardized in our study, which might have altered absorption and bioavailability rates of diclofenac.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that various physiological factors could contribute to interindividual differences in drug disposition after oral application. The different gastric acidity in fasted and fed conditions might lead to differences in oral drug dissolution and the speed of precipitation within the gastrointestinal tract . Correspondingly, the peak plasma concentration of diclofenac under fed conditions was reported to be significantly lower and the time to peak plasma concentration was significantly longer compared to fasted conditions .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Van Den Abeele et al ., have used an updated version of TIM‐1 (TIMagc) with the aim of investigating the intraluminal behaviour of diclofenac in the fasted and fed state. The results obtained from the in vitro setup were compared with intraluminal and systemic data collected from healthy volunteers after the administration of diclofenac tablets along with 240 ml of water.…”
Section: Compartmental Methods Using Cellular Membranesmentioning
confidence: 99%
“…Delayed tablet disintegration played an important role. Similarly, Van den Abeele et al . studied the GI disposition of the IR tablet Cataflam ® (50 mg diclofenac potassium) administered with a liquid meal (Ensure ® plus).…”
Section: The Role Of Drug and Formulation On The Occurrence Of Food Ementioning
confidence: 99%
“…Van den Abeele et al . (Table ) used Cataflam ® (50 mg diclofenac potassium) tablet in vivo data as a reference for the evaluation of in vitro tools with different levels of complexity, that is USP apparatus II in combination with biorelevant media, a modified dynamic open USP apparatus IV and the TIMagc, where fed state was simulated with Ensure ® Plus. The authors concluded that all three in vitro tools provided information on intraluminal or plasma concentrations in the fed state.…”
Section: Simulating the Intraluminal Performance Of Drug Products In mentioning
confidence: 99%